2007
DOI: 10.1590/s1679-87592007000300006
|View full text |Cite
|
Sign up to set email alerts
|

Feeding-deterrent properties of diterpenes of Dictyota mertensii (Phaeophyceae, Dictyotales)

Abstract: A B S T R A C TCrude extracts of the brown seaweed Dictyota mertensii (Martius) Kützing collected at two distant and different places on the Brazilian coast, Búzios (Rio de Janeiro) and Fernando de Noronha (PE), were evaluated for defensive chemistry against the crab Pachygrapsus transversus, and the sea urchin Lytechinus variegatus. The extract from Búzios specimens of D. mertensii significantly inhibited the consumption by both P. transversus and L. varigetaus. Fractionation of the extracts of specimens of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Three alga species were identified, Dictyota ciliolata, D. mertensii and D. pinnatifida, all of which are morphologically similar and produce diverse metabolites that function as defense against feeding by many herbivores (Cronin and Hay, 1996b;Marques et al, 2006;Torrano-Silva and Oliveira, this issue; Vallim et al, 2007). A single frond was posteriorly identified as Dictyopteris plagiogramma; the data was reanalyzed without this sample and no differences were found in the results.…”
Section: Algae Biomass Fluctuationmentioning
confidence: 99%
“…Three alga species were identified, Dictyota ciliolata, D. mertensii and D. pinnatifida, all of which are morphologically similar and produce diverse metabolites that function as defense against feeding by many herbivores (Cronin and Hay, 1996b;Marques et al, 2006;Torrano-Silva and Oliveira, this issue; Vallim et al, 2007). A single frond was posteriorly identified as Dictyopteris plagiogramma; the data was reanalyzed without this sample and no differences were found in the results.…”
Section: Algae Biomass Fluctuationmentioning
confidence: 99%
“…Many reef crabs are considered algal grazers (e.g., Barry and Ehret 1993), although Kang et al (2008) reported that the decorator crab Hyastenus elongatius living in a macroalgal bed primarily consumed phytoplankton-based resources. Some algae may be unpalatable due to the production of secondary metabolites that deter grazers (Kain and Norton 1990;Vallim et al 2007). Furthermore, little is known about assimilation efficiencies of red algae, although some invertebrates are able to assimilate red algae with high efficiency (e.g., Cox and Murray 2006).…”
Section: Our δmentioning
confidence: 99%
“…Dictyota mertensii was collected from two different locations in Brazil and found to vary in its diterpene composition. 33 The dichloromethane extracts from each collection and one chromatographic fraction from each extract deterred feeding by the crab Pachygrapsus transversus. The major components in the active fractions were dictyol H 9 from the southeast coast of Brazil and epoxypachydictyol A 10 from the northeast coast, 33 indicating that the chemical defenses of this seaweed are geographically variable.…”
Section: Chemical Defense Against Herbivoresmentioning
confidence: 99%